Impact of silver addition on the superconducting performances of Bi2Sr2Ca0.925Na0.075Cu2Oy:Ag composite fibers. Issue 14 (November 2022) - Atilla, B.; Ergin, I.; Gürsul, M.; Özçelik, B.; Madre, M.A.; Sotelo, A.
Abstract: This work studies the impact of metallic Ag addition on the microstructural, electrical, superconducting, and magnetic properties of Bi2 Sr2 Ca0.925 Na0.075 Cu2 Oy . Samples with 0, 1, 3, 5 wt% were prepared from precursors produced by sol-gel method, followed by texturing through the laser floating zone ( LFZ ) technique. The normal state and residual resistivity values decrease with Ag addition up to 3 wt% (from 7.61 to 2.54, and from 1.85 to 0.25 mΩ.cm, respectively), reflecting the reduction of porosity and the improvement of grains alignment and connectivity. Irreversibility line ( IL ) shifts towards high temperature with the introduction of Ag, confirming the higher grains connectivity in Ag-containing samples. Moreover, the increase of H irr (from 28.9 to 43.1 T), H c2 (from 64.6 to 85.9 T), and J c (from 4 × 10 4 to 1.2 × 10 5 A/cm 2 ) values with Ag addition also point out to the improvement of grains connectivity and flux pinning energies induced by Ag addition.